Recent advances in our understanding of the allograft response - Hennessy, C; Lewik, G; Cross, A; Hester, J; Issa, F (Faculty Opinions, 2021)
Organ transplantation is a life-saving treatment for end-stage organ failure. However, despite advances in immunosuppression, donor matching, tissue typing, and organ preservation, many organs are still lost each year to rejection. Ultimately, tolerance in the absence of immunosuppression is the goal, and although this seldom occurs spontaneously, a deeper understanding of alloimmunity may provide avenues for future therapies which aid in its establishment. Here, we highlight the recent key advances in our understanding of the allograft response. On the innate side, recent work has highlighted the previously unrecognised role of innate lymphoid cells as well as natural killer cells in promoting the alloresponse. The two major routes of allorecognition have recently been joined by a third newly identified pathway, semi-direct allorecognition, which is proving to be a key active pathway in transplantation. Through this review, we detail these newly defined areas in the allograft response and highlight areas for potential future therapeutic intervention.